"\\left(D^{2}+2 D D^{\\prime}+D^{\\prime 2}\\right) z=e^{(x+2 y)}+\\sinh(x+y)"
The auxiliary equation is "m^{2}+2m + 1 = 0"
"\\begin{array}{l}\n(m+1)^{2}=0 \\\\\n\\Rightarrow m_{1}=-1, m_{2}=-1 \\\\\n\\therefore \\text{The complementary function}\\\\\nC.F = f_{1}(y - x) + x f_{2}(y - x) \\\\\n\\end{array}"
Let, the particular integral be
"P.I = P.I_{1}+P.I_{2}\\\\\n\\begin{aligned}\nP.I_{1}&=\\frac{1}{D^{2}+2 DD'+D'^{2}} \\cdot e^{(x+2 y)} \\quad\\left(D = 1, D' = 2\\right)\\\\\nP.I_{1}&=\\frac{1}{9} e^{(x+2y)}\n\\end{aligned}"
"\\begin{aligned}\nP.I_{2}&=\\frac{1}{D^{2}+2 D D^{\\prime}+D^{2}} \\cdot \\sinh (x+y) \\\\\n&=\\frac{1}{D^{2}+2 D D^{\\prime}+D^{2}}\\left[\\frac{e^{(x+y)}-e^{-(x+y)}}{2}\\right]\\\\\n&=\\frac{1}{2}\\left[\\frac{1}{D^{2}+2 D D^{\\prime}+D^{\\prime 2}} \\cdot e^{(x+y)}-\\frac{1}{D^{2}+2 D D^{\\prime}+D^{\\prime 2}} \\cdot e^{-(x+y)}\\right]\\\\\n& \\qquad\\qquad \\{D = 1, D' = 1\\} \\qquad\\qquad\\qquad \\{D =-1, D'=-1\\}\\\\\n&=\\frac{1}{2}\\left[\\frac{e^{x+y}}{4}-\\frac{e^{-(x+y)}}{4}\\right]\\\\\nP.I_{2}&=\\frac{1}{8}\\left[e^{(x+y)}-e^{-(x+y)}\\right]=\\frac{1}{4} \\sinh (x+y)\n\\end{aligned}"
The complete solution is,
"z=f_{1}(y-x)+x f_{2}(y-x)+\\dfrac{e^{x+2 y}}{9}+\\dfrac{1}{4} \\sinh (x+y)"
Comments
Leave a comment